MANAJEMEN SISTEM PENGEMBANGAN PENDIDIKAN MENENGAH UNIVERSAL MENUJU WAJIB BELAJAR 12 TAHUN DI KABUPATEN PESISIR SELATAN - Sahnan, Muhammad (Pelita Bangsa Pelestari Pancasila, 2017)
Management emphasis on the human aspect as actors and policy implementers. In accordance with the concept of management, that person’s success or failure depends on the leadership of the extent to which he succeeded in managing the human resources that exist on organisation. Existing human resources should be managed effectively and be able to work together. Specifically examines the efforts of management in conjunction with management functions, can be implemented, especially in practices relating to the planning, implementation, and supervision. The results showed bring: (1) planning development program Universal Intermediate Education towards compulsory education 12 years in the South Coastal District of West Sumatra, beginning with the formulation of the vision and mission, requirements analysis, and preparation of planning, (2) the implementation of development programs towards reasonable Universal Intermediate Education compulsory education 12 years in the District South coast of West Sumatra has a procedure, namely organizing, parties involved in the development of intermediate education programs, identify the source of funds in the implementation of development programs and determining technique toward reasonable Universal Intermediate Education compulsory education 12 years, (3) Monitoring the Development Programme Universal Intermediate Education headed compulsory education 12 years in Coastal District South West Sumatra include monitoring and evaluation, and (4) Model Development System Management Universal Intermediate Education to the compulsory education 12 years on the South Coast, applying the principles of management, including planning, implementation, monitoring. In formulating planning beforehand adapt to change and analyze the needs doing SWOT analysis involving stakeholders (interested parties). In practice always forward commitment, cooperation, and team work is solid. Supervision is carried out through monitoring and evaluation.